1992
DOI: 10.1136/ard.51.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Bone abnormalities and severe arthritis in pachydermoperiostosis.

Abstract: Two patients with pachydermoperiostosis were studied in whom the predominant features at presentation were severe and disabling knee and ankle joint pain in association with distal long bone pain. Analysis of synovial fluid from the knee joints showed non-inflammatory changes. In one patient a bicortical iliac crest bone biopsy specimen, taken after labelling with A radiological examination showed a periosteal reaction along the distal ulnae, tibiae, and fibulae and a bone scan using labelling with strontium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 9 publications
0
17
0
4
Order By: Relevance
“…These bone changes are not a primary neoplasia or metastatic bone lesions (Lenehan and Fetter, 1985;Johnson et al, 1995;Morrison, 2002;Montgomery, 2003;Piermattei et al, 2006). Although the joints are not affected, the range of joint motion may become diminished because of periarticular soft tissue swelling (Montgomery, 2003;Piermattei et al, 2006); however, inflammatory changes in the synovial membrane of swollen painful joints were reported in humans (Cooper et al, 1992).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
“…These bone changes are not a primary neoplasia or metastatic bone lesions (Lenehan and Fetter, 1985;Johnson et al, 1995;Morrison, 2002;Montgomery, 2003;Piermattei et al, 2006). Although the joints are not affected, the range of joint motion may become diminished because of periarticular soft tissue swelling (Montgomery, 2003;Piermattei et al, 2006); however, inflammatory changes in the synovial membrane of swollen painful joints were reported in humans (Cooper et al, 1992).…”
Section: What Is Hypertrophic Osteopathy (Review Of the Literature)mentioning
confidence: 99%
“…Risedronate sodium has been reported to work on osteoclasts, resulting in a decrease in urinary NTx. 10 Cooper et al 11 reported an increased number of osteoclasts in the bone of PDP patients. It is considered that risedronate sodium inhibited the osteoclasts in the bones of our PDP patient.…”
Section: Discussionmentioning
confidence: 98%
“…In almost 40% of patients, this disease is complicated by joint effusion, but the symptoms are not particularly severe 8 and only a few cases experience severe joint pain. 9 Histological examinations of synovia in those patients showed hypercellularity and vascular thickening or venous dilatation without inflammation. 9,10 In addition, no inflama b c d matory signs were detected in the synovial fluid.…”
Section: Discussionmentioning
confidence: 99%
“…9 Histological examinations of synovia in those patients showed hypercellularity and vascular thickening or venous dilatation without inflammation. 9,10 In addition, no inflama b c d matory signs were detected in the synovial fluid. In some cases, patient's presented with acute-onset arthralgia derived from pseudogout.…”
Section: Discussionmentioning
confidence: 99%